SARS-CoV-2 Affects Thyroid and Adrenal Glands: An 18F-FDG PET/CT Study - Chiara Lauri; Giuseppe Campagna; Andor W. J. M. Glaudemans; Riemer H. J. A. Slart; Bram van Leer; Janesh Pillay; Marzia Colandrea; Chiara Maria Grana; Antonio Stigliano; Alberto Signore (Biomedicines, 2023)
Background: Since most endocrine glands express ACE-2 receptors and can be infected by SARS-CoV-2 virus, this retrospective multicentre observational study aims to assess the metabolic activity of thyroid and adrenal glands of COVID-19 patients by 18F-FDG PET/CT. Methods: We retrospectively evaluated the 18F-FDG PET/CT scans of COVID-19 patients admitted by three different centres, either in a low-intensity department or in the intensive care unit (ICU). A visual assessment and a semi-quantitative evaluation of areas of interest in thyroid and adrenal glands were performed by recording SUVmax and SUVmean. The 18F-FDG PET/CT uptake in COVID-19 patients was compared with those observed in normal age-matched controls. Results: Between March 2020 and March 2022, 33 patients from three different centres (twenty-eight patients in a low-intensity department and five patients in ICU), were studied by 18F-FDG PET/CT during active illness. Seven of them were also studied after clinical remission (3–6 months after disease onset). Thirty-six normal subjects were used as age-matched controls. In the thyroid gland, no statistically significant differences were observed between control subjects and COVID-19 patients at diagnosis. However, at the follow-up PET/CT study, we found a statistically higher SUVmax and SUVmean (p = 0.009 and p = 0.004, respectively) in the thyroid of COVID-19 patients. In adrenal glands, we observed lower SUVmax and SUVmean in COVID-19 patients at baseline compared to control subjects (p < 0.0001) and this finding did not normalize after clinical recovery (p = 0.0018 for SUVmax and p = 0.002 for SUV mean). Conclusions: In our series, we observed persistent low 18F-FDG uptake in adrenal glands of patients at diagnosis of COVID-19 and after recovery, suggesting a chronic hypofunction. By contrast, thyroid uptake was comparable to normal subjects at disease onset, but after recovery, a subgroup of patients showed an increased metabolism, thus possibly suggesting the onset of an inflammatory thyroiditis. Our results should alert clinicians to investigate the pituitary–adrenal axis and thyroid functionality at the time of infection and to monitor them after recovery.